Clinical Management of End-Stage Renal Disease Patients on Dialysis Receiving Radioactive Iodine Treatment. (December 2021) - AlSadi, Rahaf; Aziz, Landon C.; Bohan, Michael; Dewji, Shaheen; Bouhali, Othmane; Djekidel, Mehdi
Abstract : Purpose: Radioactive iodine (RAI) is used to treat thyroid cancer patients with a clear paradigm for most patients. End-stage renal disease (ESRD) patients pose several challenges when undergoing RAI treatment, primarily due to the lack of renal clearance. We retrospectively report our experience with RAI treatment in a cohort of patients with ESRD and provide a set of recommendations on aspects such as the need for adjusted dose activity, balancing scheduling between RAI therapy and dialysis, and radiation safety precautions. Patients and Methods: In this study, we report on 5 patients (6 cases), with ESRD on dialysis, treated with RAI for thyroid cancer. Retention measurements to determine individual biological clearance of RAI from the patient's body before and after dialysis sessions were assessed using external exposure dose rates measured at 1 m. Results: Delayed biological clearance of RAI, after the first hemodialysis session, resulted in a longer RAI effective half-life as a consequence of longer retention periods, consistent with observations reported in scientific literature. To achieve a much closer radiation exposure compared with a nondialysis patient, one would recommend administering ~20%–30% of the dose activity normally administered to a thyroid cancer patient based on their medical history, histopathology, and uptake with the appropriate dialysis schedule. Conclusions: Special precautions should be taken with the administration of RAI in ESRD patients by adjusting the prescribed dose activity, dialysis sessions, and paying special attention to wastes. Pooling data from multiple centers may be useful to build a consensus and substantiated recommendations.